An Examination of Geomagnetic Induction in Submarine Cables - Boteler, David H.; Chakraborty, Shibaji; Shi, Xueling; Hartinger, Michael D.; Wang, Xuan (Space Weather, 2024)
Submarine cables have experienced problems during extreme geomagnetic disturbances because of geomagnetically induced voltages adding or subtracting from the power feed to the repeaters. This is still a concern for modern fiber‐optic cables because they contain a copper conductor to carry power to the repeaters. This paper provides a new examination of geomagnetic induction in submarine cables and makes calculations of the voltages experienced by the TAT‐8 trans‐Atlantic submarine cable during the March 1989 magnetic storm. It is shown that the cable itself experiences an induced electromotive force (emf) and that induction in the ocean also leads to changes of potential of the land at each end of the cable. The process for calculating the electric fields induced in the sea and in the cable from knowledge of the seawater depth and conductivity and subsea conductivity is explained. The cable route is divided into 9 sections and the seafloor electric field is calculated for each section. These are combined to give the total induced emf in the cable. In addition, induction in the seawater and leakage of induced currents through the underlying resistive layers are modeled using a transmission line model of the ocean and underlying layers to determine the change in Earth potentials at the cable ends. The induced emf in the cable and the end potentials are then combined to give the total voltage change experienced by the cable power feed equipment. This gives results very close to those recorded on the TAT‐8 cable in March 1989. Plain Language Summary Submarine cables carry a significant amount of international internet traffic, so any disruption to their operation could have widespread consequences. In the past, trans‐Atlantic phone calls have been heard alternately as shrieks and whispers as geomagnetically induced voltages added or subtracted from the power feed for the cable repeaters used to amplify the signals. Modern submarine cables transmit the signals along optical fibers but still have a copper conductor along the cable to carry power to the repeaters, so continue to be subject to voltages induced by disturbances of the Earth's magnetic field. This paper re‐examines the process of geomagnetic induction in the sea and submarine cables. It is shown that this involves both the production of an induced electromotive force (emf) in the cable itself as well as induction in the seawater that leads to a change in the potential of the land at each end of the cable. Example calculations are made for the TAT‐8 trans‐Atlantic cable and compared to measurements made on the cable during 13 and 14 March 1989, the largest magnetic storm of the 20th century. Key Points Geomagnetic disturbances induce electric fields in both the sea and in submarine cables Earth potentials are produced by the geoelectric coast effect at each end of a cable route Voltages experienced by submarine cables are due to both the induced electric fields and earth potentials at the ends